Efektivitas Pembelajaran Berbasis Riset pada Mata Kuliah Hikmat al-Tasyri - Arumawan, Muhammad Muhsin; Yasri, Hayyun Lathifaty (Jurnal Penelitian Pendidikan Islam, 2020)
Research-based learning is a learning approach that can stimulate critical thinking skills and improve learning outcomes. In line with this, this study aims to determine the effectiveness of research-based learning in the Hikmatu-t-Tasyri 'lecture. This research was conducted using qualitative methods with a period of 6 months. The data collection techniques used were observation, distributing questionnaires and using supporting documentation. The collected data is then processed through data reduction, data display and conclusion drawing. The results of this study indicate that the implementation of research-based learning in the Hikmatu-t-Tasyri 'course is proven to be good. This is evidenced by the results of distributing questionnaires regarding student assessments of the effectiveness of research-based learning with the 5 indicators mentioned above which obtained an average result in the Good category.